2012
DOI: 10.2147/dnnd.s19839
|View full text |Cite
|
Sign up to set email alerts
|

Walking impairment in patients with multiple sclerosis – a new therapeutic approach and clinical potential of dalfampridine extended release tablets

Abstract: Walking impairment is a clinical hallmark of multiple sclerosis (MS) that has been under-recognized as a therapeutic target for pharmacologic intervention. The development and approval of dalfampridine extended release tablets (dalfampridine-ER; known as prolonged-, modified, or sustained-release fampridine outside the USA), 10 mg taken twice daily, to improve walking in patients with MS, fills a previously unmet need. In three randomized, double-blind, placebo-controlled trials, dalfampridine-ER improved walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…Notably, improvement did not vary substantially with baseline severity of walking impairment, as indicated by mMSWS-12 scores. These results are consistent with reports from the literature that showed that walking improvement among patients treated with dalfampridine-ER was independent of demographic variables, disease characteristics, and level of disability [ 11 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, improvement did not vary substantially with baseline severity of walking impairment, as indicated by mMSWS-12 scores. These results are consistent with reports from the literature that showed that walking improvement among patients treated with dalfampridine-ER was independent of demographic variables, disease characteristics, and level of disability [ 11 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since funding was secured for this trial, there has been increasing interest in prescribing Fampyra to increase gait speed and thus an additional strata was created to avoid having an imbalance of people on Fampyra (dalfampridine;prolonged-release fampridine tablets) in one of the groups [83,84]. …”
Section: Methodsmentioning
confidence: 99%